2023
DOI: 10.1186/s12885-022-10421-w
|View full text |Cite
|
Sign up to set email alerts
|

Umbrella review of basket trials testing a drug in tumors with actionable genetic biomarkers

Abstract: Background The utilization of basket trials in oncology has gained popularity because of the drive for precision medicine and the increasing ease of genetically profiling tumors. However, it is unknown if this has translated into patient benefit, either through higher response rates because of precision treatment or because of increasing options for less-common tumor types that are less represented in oncology drug trials. We sought to characterize basket studies for oncology drugs targeting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…( 11 ) and Haslam et al. ( 12 ), all phase Ib or phase II basket trials identified in this review were single-arm non-randomized open label studies, and 91% (133/146) of the trials had objective response rate as either a primary or secondary endpoint. Further information about the review of basket trials in practice and the risk of bias are presented in the Supplementary File 1 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…( 11 ) and Haslam et al. ( 12 ), all phase Ib or phase II basket trials identified in this review were single-arm non-randomized open label studies, and 91% (133/146) of the trials had objective response rate as either a primary or secondary endpoint. Further information about the review of basket trials in practice and the risk of bias are presented in the Supplementary File 1 .…”
Section: Resultsmentioning
confidence: 93%
“…A more recent systematic review by Haslam et al. ( 12 ) focused on basket trials in oncology with published results in which they characterized the correlation between the size of a basket and the incidence of the respective tumor. Another recent review by Haslam et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite similarities among the different cohorts, there is an expectation that the treatment effect might differ. 4 To facilitate the evaluation of these therapies, basket trial protocols have been used to assess the combination of several molecular markers and targeted therapies across multiple subgroups. 1,3 In this setting, a basket trial typically involves evaluating a single therapy targeting a group of patients who share a common clinical or genetic feature or biomarker, regardless of their histology type (Figure 1).…”
Section: Master Protocol Designmentioning
confidence: 99%
“…The nature of basket trials, in which eligible patients with a common biomarker are recruited independently of tumour type, suggests there may be heterogeneity within tumour histology. 4 One way to account for heterogeneity is to analyze each tumour type separately. However, sample sizes vary among cohorts, and studies for some cancer types -particularly rare ones -may suffer from poor recruitment and limited information on response rates.…”
Section: Heterogeneity In Basket Trialsmentioning
confidence: 99%